Gambaran Standar Perencanaan dan Pengadaan Obat di Instalasi Farmasi RSU Kota Tangerang Selatan Tahun 2017 - Nurwulan adi Ismaya; Tri Okta Ratnaningtyas; Rani Riskha Wahyuni (Edu Masda Journal, 2019)
Selection and Procurement are the crucial things in drug management system and they become primary things to do to avoid drug emptiness. The objective oh this research is to know the effectiveness and effeciency of drug  management in Selection and Procurement stage at South Tangerang City General Hospital  in 2017.  The methods of this research is descriptive research design with retrospective data retrieval. Data in the form of qualitative and quantitative accompanied by interviews with related parties. Selection and Procurement Phase in the measurement of its efficiency by using the indicator that issued by MOH RI (2002). The results showed that in the selection stage of drug management at Tangerang Selatan Public Hospital in 2017 showed it has not been effective, it has seen from the measurement on the indicator of conformity of the drug item with the DOEN showed the value of 20.90% below the standard value of 49%. Then at the Procurement stage showed effective results, it has seen from the Frequency of procurement of medicinal items each year showed frequency results as much as 1-19x / year (Medium standard), the frequency of error invoice / order letter as much as 2 times the value of comparison 1-9 times, and the frequency of delayed payment by the hospital 15 times from the comparison value 0-25 times. Drug procurement in South Tangerang General Hospital has been effective, it showed from the Frequency of procurement of medicinal items per year, the frequency of error invoice / order letter, and the frequency of delayed payment by the hospital. Based on this results, the Drug Procurement in South Tangerang General Hospital has been effective, but the selection hasn’t  effective yet.